Third trimester fetal growth and measures of carbohydrate and lipid metabolism in umbilical venous blood at term. Issue 1 (1st January 1997) - Spencer, John A D; Chang, Tou C; Crook, David; Proudler, Anthony; Felton, Carl V; Robson, Stephen C; Hauesler, Martin
Abstract : AIM: To compare measures of carbohydrate and lipid metabolism in umbilical venous blood after birth at term in pregnancies with normal and retarded fetal growth during the third trimester. METHODS: Three groups of pregnancies reaching term, in which fetal growth had been prospectively monitored by repeated ultrasound measurements during the third trimester, were studied. Sequential fetal abdominal circumference measurements remained above the 10th centile in 42 (normal size, normal growth group), below the 10th centile but did not depart further than 1.5 SD (small, normal growth group), or below the 10th centile and subsequently fell away by more than 1.5 SD before delivery (small, growth retarded group). Birthweight, neonatal morphometric measures (ponderal index, mid arm:head circumference ratio, subscapular and triceps skinfold thickness), umbilical venous blood concentrations of glucose, insulin, pro-insulin, des 31, 32 proinsulin, total cholesterol, free cholesterol, cholesterol ester, triglycerides, lipoprotein (a), apolipoprotein A-1 and apolipoprotein B were measured. RESULTS: The median birthweight of the three groups was significantly different (3570, 2569, and 2277 g, respectively). Median values of ponderal index and mid arm:head circumference ratio were significantly lower in the small, growth retarded group and did not differ between the small and normal size groups with normal growth. Both groups with small fetuses had significantly lower mean glucose and cholesterol ester concentrations, and higher mean free cholesterol:cholesterol ester ratios, compared with the normal size, normal growth group. The group showing fetal growth retardation had mean total cholesterol and mean cholesterol ester concentrations that were significantly lower than those of both the other two groups. Mean des 31, 32 proinsulin concentrations were low in both groups of small fetuses, but only significantly so in the group without fetal growth retardation. Mean insulin, proinsulin, free cholesterol, triglycerides, lipoprotein(a), apolipoprotein A-1, apolipoprotein B concentrations and the ratio of A-1:B were similar in all three groups. CONCLUSION: The similarity in the umbilical venous blood carbohydrate and lipid profile at term between pregnancies with documented third trimester fetal growth retardation and those with "genetically" small babies argues against a major role for intrauterine nutritional deprivation as a cause for the association between birthweight and subsequent adult disease.